- AKTA JUAL BELI YANG DIBUAT OLEH PPATS BERKAITAN DENGAN PROSES PENDAFTARAN TANAH (STUDI KASUS PPATS KECAMATAN BATUJAYA KABUPATEN KARAWANG): - - Astrid Utari Kemala; Metty Soletri (Reformasi Hukum Trisakti, 2023)
According to the mandate of the UUPA, which is mentioned in Article 19 paragraph (1) of Law No. 5/1960 Jo. and Article 3 letter an of PP 24/1997, the goal of land registration is to ensure legal certainty. In this instance, the role of PPAT is one of the institutions that promotes the attainment of the objective of land registration. But in practice, many continue to employ PPATS services in place of PPAT. Problem statement: Does the PPATS play the same role with PPAT ? How about the legal status of sales purchase deed made by PPATS to land certified. A normative-juridical research methodology was used, with the nature of qualitative research, literature study and the primary data is interviewed. Data analysis is done by qualitative methods with use interview data result. The conclusion is carried out by the deductive method. The research results, discussion and conclusion that act of transfer land rights need land registration to obtain legal certainty. Legal consequences if land obtained through buying and selling but not immediately registered is not meeting the clear legality. The transfer of land rights carried out by PPATS is not continued until the process of tittle transfer document.